2021
DOI: 10.21203/rs.3.rs-492643/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of Radiographic And Clinical Outcomes Observed After Adult Spinal Deformity Correction Using Iliac Screw Versus S2-Alar-Iliac Screw

Abstract: Background: To date, there is a paucity of reports clarifying the change of spinopelvic parameters in patients with adult spinal deformity (ASD) who underwent long segment spinal fusion using iliac screw (IS) and S2-alar-iliac screw (S2AI) fixation.Methods: A retrospective review of consecutive patients underwent deformity correction surgery for ASD between 2013 and 2017 was performed. Patients were divided into two groups based on whether IS or S2AI fixation was performed. All radiographic parameters were mea… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 23 publications
2
2
0
Order By: Relevance
“…Additionally, the post-operative ODI (31.7 19.2) was significantly lower than the pre-operative ODI (66.2 11.1) (high statistical significance; p-value 0.001). This was in agreement with Luo et al, 8 who revealed that both VAS score for back and leg and ODI were significantly improved in S2AI group.Also, Elder et al, 11 revealed that VAS score as well as ambulatory status was significantly improved in S2AI group.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Additionally, the post-operative ODI (31.7 19.2) was significantly lower than the pre-operative ODI (66.2 11.1) (high statistical significance; p-value 0.001). This was in agreement with Luo et al, 8 who revealed that both VAS score for back and leg and ODI were significantly improved in S2AI group.Also, Elder et al, 11 revealed that VAS score as well as ambulatory status was significantly improved in S2AI group.…”
Section: Discussionsupporting
confidence: 93%
“…This was in agreement with Luo et al, 8 who revealed that in S2AI group the mean difference VAS of back were 4.46 and for leg were 3.99. Also, Ishida et al, 10 reported that in S2AI group the mean difference VAS was 2.6 + 2.0.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations